Recurrence of Breast Cancer After Primary Treatment: A Matched Comparison Study of Disease-Free Survival in Women Who Do and Do Not Receive Adjunctive Naturopathic Oncology Care. (December 2021) - Standish, L. J.; Sweet, E.; Kim, Eunjung; Dowd, F.; McLaughlin, Ryan; Chiang, P.; Dale, L.; Gaul, M.; Andersen, M. R.
Purpose: To compare disease free survival experienced by women who received usual oncologic care compared to a cohort of women who received naturopathic oncology care in addition to usual care. Methods: Women with breast cancer who received naturopathic oncology (NO) care in Western Washington State (WA) (N = 176) were recruited to a prospective study of clinical health-related quality of life outcomes and then matched to women who received usual care (UC) only (N = 334). Results: Among 510 women with breast cancer stages 1 to 3, a total of 50 women (10%) experienced a disease-free survival (DFS) ending event within the observation period; 23 (6.8% of those in the UC cohort, and 27 (15.3% of those in the NO cohort ( P < .05). Although, women in the 2 cohorts received similar surgical, chemotherapy, and radiation treatment, women with breast cancer who received naturopathic oncology adjunctive care were less likely to use anti-estrogen therapy, and experienced poorer DFS (logrank test, P < .05). However, differences in DFS could not be shown to be due to cohort differences in anti-estrogen therapy, baseline HRQOL, or naturopathic oncology therapies prescribed. The stage 3 women in the naturopathic oncology group had more advanced disease at diagnosis. They were more likely to have 5 or more metastatic lymph nodes at baseline (18.5%) compared to their usual care matched control group (13%). Women in the naturopathic oncology group also had higher grade tumors at diagnosis. Conclusions: Results show that recurrence of breast cancer was associated with more advanced malignant lymph node involvement; and that naturopathic oncology services provided in 2009-2015 did not improve disease-free survival in these high-risk breast cancer patients.